The FIT FIRST 10 dose-response study: evaluation of implementation outcomes - Koch, Sofie; Eckert, Caroline; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie; Cimenti, Chiara; Larsen, Malte Nejst; Krustrup, Peter; Skov Christiansen, Lars Breum (Frontiers in Sports and Active Living, 2025)
IntroductionIncreasing physical activity (PA) levels among children is critical to mitigate health risks associated with physical inactivity. Schools have been highlighted as ideal setting for promoting PA. However, existing school-based PA programs often face implementation challenges. The FIT FIRST 10 (FF10) multi-sport program has been introduced in Denmark, aiming to increase PA and to enhance children's health, fitness, and well-being. This study evaluates the implementation of the FF10 program for 2nd and 3rd graders.Materials and methodsThe FF10 program was implemented in a 20-week cluster randomized controlled trial across 27 schools. Schools were assigned to a control arm or intervention arms receiving either 3 (full dose) or 1.5 (half dose) FF10 40-min lessons weekly. Teachers received a one-day training session, comprehensive manuals, and necessary equipment. Data were collected from teachers via logbooks documenting implementation fidelity, and an online questionnaire assessing program acceptability, appropriateness, and feasibility, and teachers' capability, opportunity, and motivation for implementing the FF10 program.ResultsA total of 18 intervention schools with 36 classes participated in this study. Program fidelity was high in both intervention groups (2.8 and 2.0 session/week for full and half-dose, respectively). Confidence intervals indicated no differences between the two intervention groups for any outcomes. Teachers (n = 32) in both groups rated FF10 moderately acceptable, appropriate, and feasible (3.5–4.0 out of a potential maximum of 5). Both groups exhibited moderate physical and psychological capabilities (3.5–4.0) and high social opportunities (>4.0), but poor motivation scores (<3.5), particularly regarding the perceived benefits and automatization in delivering the FF10 program.ConclusionThe FF10 program was almost delivered as intended, but time constraints, limited facilities, and modest teacher motivation might have hindered implementation. Reducing the program's dosage did not improve implementation outcomes, emphasizing the need for ongoing support to boost teacher motivation and integration of the program into school timetables.